Hornification에 따른 TOCN 에어로겔 흡착 거동의 변화 - 김선유; Suhnue Kim; 이가현; Gahyeon Lee; 유동훈; Dong Hoon You; 김형섭; Hyungsup Kim (한국섬유공학회지, 2025)
In this study, the influence of carboxymethyl cellulose(CMC) on the structure and adsorption behavior of TEMPO-oxidized cellulose nanofibril(TOCN) based aerogel was investigated. The rheological and precipitation observations strongly supported the prevention of TOCN hornification by CMC. The SEM images of prepared aerogel confirmed the dense pore structure owing to low hornification of TOCN. The adsorption behaviors of the fabricated aerogels were isothermally and kinetically studied using methylene blue(MB) as a cationic model dye. CMC added TOCN aerogel showed the highest maximum adsorption capacity (208.07 mg·g -1 ) towards MB due to the dense pore structure and maintained the adsorption performance after 5 repeated adsorption cycles. The effect of TOCN hornification was an important parameter on the TOCN aerogel structure and adsorption performance.